EDAPHIC AND CLIMATIC RELATION AND ITS INFLUENCE ON THE COMPOSITION FLORISTIC LOWER STRATUM IN A FLOODPLAIN FOREST, PARÁ, BRAZIL - Braga,Elayne Oliveira (2016)
ABSTRACT This work evaluated the soil and climate influence in the floristic composition of the lower stratum in a floodplain forest in the environmental protection area of Combu Island, in Belém, Pará. From February to April (high rainy period) and from May to July (less rainy period), all individuals with height ≤ 1 m were sampled and identified in four plots of 20 x 20 m divided into subplots of 1 m2. A sample of soil per plot was collected at the depth of 20 cm in the months of April and July. The relationship between floristic with edaphic and climatic conditions was evaluated by a canonical correspondence analysis (CCA). The floristic composition between the two studied periods was similar. Differently, the physico-chemical soil composition showed variation between the two periods. The CCA indicated a significant correlation between the distribution of species and edaphic factors, although most species were not influenced by soil variables, in particular the most abundant ones. Some species showed a relationship with In and fine sand, indicating the existence of preferential sites for some species.